Echocardiographic abnormalities in children with obstructive breathing disorders during sleep - Weber, Silke Anna Theresa [UNESP]; Montovani, Jair Cortez [UNESP]; Matsubara, Beatriz [UNESP]; Fioretto, José Roberto [UNESP] (Sociedade Brasileira de Pediatria, 2007)
Objectives: To assess cardiac morphology and function by means of echocardiograms of children with obstructad breathing while asleep.Methods: the study enrolled 40 children of both sexes, aged from 3 to 11 years; 30 of them had obstructed breathing during sleep (group I) and 10 children were healthy controls (group II). The two groups were similar in terms of sex, age, weight and height. The 40 children underwent echocardiogram, viewing all four chambers during systole and diastole, paying special attention to the right ventricle (RV). These data were compared by means of Student's t test (p < 0.05).Results: In group I, increased diameter and area of the right ventricle were observed during both systole and diastole. There was less variation in RV area between systole and diastole. Reduced left ventricle (LV) diastolic diameter was also observed, together with reduced ejection fraction and reduced contraction.Conclusions: the morphological and functional cardiac abnormalities observed in the RV and LV suggest that, in children, obstructed breathing during sleep can lead to cardiovascular repercussions. These abnormalities may expose these children to increased anesthetic and surgical risks.